Silencing the opposition : how the U.S. government suppressed freedom of expression during major crises - Smith, Craig R. (State University of New York Press, 2011)
Annotation This title examines major challenges to the First Amendment and focuses on the extremely important paradigm shift of freedom of expression in the post-9/11 era.
Keywords: Freedom of speech -- United States -- History.; Political oratory -- United States -- History.; Liberté d'expression -- États-Unis -- Histoire.; Éloquence politique -- États-Unis -- Histoire.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Freedom of speech; Political oratory; United States; History